Evaluation of Electric Fences for their Efficacy in Controlling Elephant Damage in Northern West Bengal and Suggesting Improvements - Chauhan, N. P. S.; Chowdhury, Sushant (Indian Forester, 2002)
An evaluation of 49 existing power fences in Northern Bengal that have been established from 1982 to 1997 to keep elephants out from the plantation, human habitations in various ranges and tea gardens and crop fields, was carried out. Fences varied from single strand to 6 strands but majority were in the category of 2-3 strands. There was a general flaw of speciesspecific design for elephants in terms of energizing the surroundings of the fence posts, which exposed them for their vulnerability to uprooting or pushing over. Corroding GI wires and improper insulation materials were the reasons for power loss varying from 0.5-7.3 kV between source to the end. In 18% cases (n=9) poor battery maintenance was the reason for low power output to shock the elephants. The energizer output at negative and positive terminals varied from 1.6-9.6 kV and 1.2-8.5 kV respectively. The leaking at earthing points varied from 0-1.9 kV, which is quite substantial. The technical and maintenance problems were invariably acute in nearly all fences, yet 26% were effective in output terms. The authors recommend initiation of stakeholder participation for installation and maintenance of fences, as large number of poorly maintained fences could be sources of learning for elephants to breach the fence line repeatedly. Important recommendations for design, maintenance and periodic training need to front line staff and stakeholders are suggested.